2019
DOI: 10.1038/s41467-019-10383-x
|View full text |Cite
|
Sign up to set email alerts
|

Homochirality in biomineral suprastructures induced by assembly of single-enantiomer amino acids from a nonracemic mixture

Abstract: Since Pasteur first successfully separated right-handed and left-handed tartrate crystals in 1848, the understanding of how homochirality is achieved from enantiomeric mixtures has long been incomplete. Here, we report on a chirality dominance effect where organized, three-dimensional homochiral suprastructures of the biomineral calcium carbonate (vaterite) can be induced from a mixed nonracemic amino acid system. Right-handed (counterclockwise) homochiral vaterite helicoids are induced when the amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 65 publications
1
31
0
Order By: Relevance
“…11f ). 149 High-resolution microscopy demonstrated that both achiral (no additive) and spirally oriented curved platelets (with amino acid) had a nanoparticle substructure ( Fig. 11g ).…”
Section: Manipulation Of Hierarchical Chiral Self-assemblymentioning
confidence: 99%
“…11f ). 149 High-resolution microscopy demonstrated that both achiral (no additive) and spirally oriented curved platelets (with amino acid) had a nanoparticle substructure ( Fig. 11g ).…”
Section: Manipulation Of Hierarchical Chiral Self-assemblymentioning
confidence: 99%
“…For example, the unique properties of bone and dental enamel come out from its distinct hierarchical structure at different length scales. [ 1–3 ]…”
Section: Introductionmentioning
confidence: 99%
“…For example, the unique properties of bone and dental enamel come out from its distinct hierarchical structure at different length scales. [1][2][3] Materials and tissue engineering face a sophisticated challenge to create the architecture of biological tissues in terms of physical and chemical characteristics. Therefore, understanding the mechanism of periodic patterns formation is of great interest for fabricating biomimetic materials.…”
mentioning
confidence: 99%
“…With the ability to govern the enantioselectivity of the global chirality of the supramolecular assemblies in a nonracemic mixture of the molecular environment, the MR principle is believed to have a profound impact on the origin of biological homochirality, in addition to its important role in achieving chiral supramolecular materials with desired functionalities. , Experimentally, the MR effect can be identified by nonlinear changes of CD activities, or nonlinear distributions of left-/right-handedness of supramolecular nanostructures, as a function of the ee of the chiral monomers. There have been a lot of reports on the MR effect observed in various supramolecular assemblies in solution phase or at two-dimensional (2D) interfaces, and very recently in the nucleation and growth of biomineral suprastructures . However, whether and how the MR principle can apply to the inorganic nanoparticle assembly system remains unexplored to date …”
mentioning
confidence: 99%
“…There have been a lot of reports on the MR effect observed in various supramolecular assemblies in solution phase 36 or at two-dimensional (2D) interfaces, 41−43 and very recently in the nucleation and growth of biomineral suprastructures. 44 However, whether and how the MR principle can apply to the inorganic nanoparticle assembly system remains unexplored to date. 38 In this work, we demonstrate experimentally the validity of the MR principle in the chiral transfer and amplification process in molecularly mediated assembly of plasmonic nanoparticles.…”
mentioning
confidence: 99%